Kualitas Pelayanan Publik dalam Pengurusan Kartu Tanda Penduduk Elektronik (e-KTP) di Kantor Camat Parongpong Kabupaten Bandung Barat - Cynthia Reidha Purwanty; Wawan Gunawan; Indra Kristian (Universitas 17 Agustus 1945, 2024)
This study aims to evaluate the quality of public services in the management of Electronic Identity Cards (e-KTP) in Parongpong District. Using a descriptive qualitative method, data was obtained through direct observation and in-depth interviews with several sources, including the Parongpong District Head, the Head of Government and Public Service Section, service staff, and two service users. The findings indicate that the quality of public services at the Parongpong District Office is still not optimal. Several aspects need improvement, such as Tangibles (physical evidence), where the facilities do not meet the standards necessary to efficiently support the e-KTP process. Additionally, there is uncertainty in the completion of e-KTPs due to a shortage of blanks and technical disruptions on the server (Reliability), as well as insufficient assurance regarding service timeliness (Assurance). This study is expected to provide insights for improving e-KTP services in the future.